Wizualny aspekt przekazu treści religijnych w polskiej prasie katolickiej. Od teorii do praktyki (na przykładzie „Gościa Niedzielnego” i „Tygodnika Powszechnego”) - Pethe, Aleksandra (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The visual aspect of media coverage is the subject of reflection in communication science as well as in theology. The coherence of the word and the image and their relationship are constitutive elements of the Polish Catholic press. Innovation and originality of solutions consists in concrete realizations. New proposals are aimed at visualizing the content of the media. This concerns the visual-verbal relationships (mainly the cover of the writings) and verbal-visual (most articles). The dynamics of image forms and the correlation between text and image (photography) intensifies the media message and also fits in with the modern aesthetics of the press. One of the effects is the better quality and attractiveness of the „new” language of religious communication. Among the most opinion-forming Catholic writings in Poland are Katowice’s „Gość Niedzielny” and Cracow „Tygodnik Powszechny”. Care and attention to this dimension are evident in both editions. The verbal and visual plane is an important mediator in the transmission of religious, evangelistic and pastoral content.